A study on the frame of a memory-dependent derivative in a micropolar thermoelastic medium under the effect of the variable thermal conductivity. Issue 2 (1st February 2023) - Said, Samia M.
Abstract: In the present work, the 2D problem of a magneto-micropolar thermoelastic medium in the context of the dual-phase-lag model with the frame of the memory-dependent derivative is established. Normal mode analysis and an eigenvalue expansion technique are used to solve the resulting non-dimensional coupled governing equations. The variations of the physical quantities with the vertical distance are illustrated graphically. The effects of the time-delay parameter, magnetic field, rotation, and the variable thermal conductivity on the variations of different field quantities inside the half-space are analyzed graphically.